(untitled) (Medical Forum Monthly, 2024)
Objective: The aim of this study was to see the risk factors and clinical manifestations of the central nervous system tuberculosis in the patients attending teaching hospital of Gujranwala. Study Design: Observational / descriptive study Place and Duration of Study: This study was conducted at the Indoor Department of Medicine of District Teaching Hospital, Gujranwala from February 2015 to September 2015. Materials and Methods: Total 110 cases of TBM were included in our study. The clinical details of these patients were taken and particularly the details of the patient, the history (present, past related), the clinical features were recorded. Data was analyzed by SPSS v.18 and result formulated in the form of tables and figures. Results: Past history of tuberculosis was present in 23 (25.55%) patients and 10 (11.11%) had family history of tuberculosis. In 44 (48.88%) cases there were no significant risk factors. The main symptoms of brain tuberculosis were convulsions (65.60%), headache (56.25%), fever (37.5%), vomiting (25%), visual impairment (9.3%) and weakness (25%). Motor deficits were found in (37.5%), urinary incontinence in (9.3%), ptosis in (12.5%) and cranial nerve palsy in (18.75%) patients. Conclusion: The already suffering from tuberculosis was the major risk factor of Central Nervous tuberculosis. So the proper management of tuberculosis is necessary so that future risk factor for CNS tuberculosis should be reduced. Convulsions and headache were the most common symptoms of CNS tuberculosis.